Diseño de un banco de pruebas para la caracterización de un colector híbrido termo-fotovoltaico (PV/T) para las condiciones climáticas de Bogotá (2017)
"The development of new technologies, as solar photovoltaic/thermal (PV/T) hybrid collector, that allows the generation of energy taking the most of renewable resources -as solar radiation- is creating the need of starting the development of systems capable of characterizing and calculating those systems efficiencies. In this proyect, a testing bench (closed loop) was disigned and builded, according to NTC 5434-2 and NTC 4405 norms. It showed to be capable of successfully characterizing a PV/T collector, using efficient instruments without spending big amounts of money. Likewise, it was shown the notorious inffluence of solar radiation over PV/T collectors, as their efficiency drops drastically when incident solar beams do not have direct contact with collector's aperture area." -- Tomado del Formato de Documento de Grado.